2014
DOI: 10.1093/mmy/myu026
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes and melanin represent a first line of innate immunity against Candida albicans

Abstract: Melanocytes are dendritic cells located in the skin and mucosae that synthesize melanin. Some infections induce hypo- or hyperpigmentation, which is associated with the activation of Toll-like receptors (TLRs), especially TLR4. Candida albicans is an opportunist pathogen that can switch between blastoconidia and hyphae forms; the latter is associated with invasion. Our objectives in this study were to ascertain whether C. albicans induces pigmentation in melanocytes and whether this process is dependent on TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In addition, this antifungal activity against the clinical isolates, obtained from patients, was higher than the reference strains ( Figure 3 ). In previous work (Tapia et al, 2014), we demonstrated that melanin participates in a first line of the innate immune response of melanocytes stimulated with Candida extracts, by cell melanisation, which is related to the expression of Toll Like Receptor 4 (TLR4). Therefore, these results support the idea that human melanin can represent a mechanism of antimicrobial defense against fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this antifungal activity against the clinical isolates, obtained from patients, was higher than the reference strains ( Figure 3 ). In previous work (Tapia et al, 2014), we demonstrated that melanin participates in a first line of the innate immune response of melanocytes stimulated with Candida extracts, by cell melanisation, which is related to the expression of Toll Like Receptor 4 (TLR4). Therefore, these results support the idea that human melanin can represent a mechanism of antimicrobial defense against fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin has also been demonstrated to have antimicrobial properties[50]. While early studies demonstrated that C. albicans negatively regulates transcription of melanogenesis genes, more recent study has shown that melanocytes may recognize C. albicans via Toll Like Receptor 4 to increase melanization and inhibit infection (Figure 1)[51,52]. …”
Section: Innate Immune Response To C Albicansmentioning
confidence: 99%
“…IL-23 acts on dermal γδ T cells to drive IL-17 production in the skin, leading to anti- C. albicans resistance through the presumed activation of neutrophils and antimicrobial peptides such as β-defensins[14]. In addition, melanocytes in the basal epidermis can also recognize C. albicans via TLR-4 to drive production and release of melanin granules, which are antimicrobial in nature[52]. Finally, Langerhans cells of the epidermis can suppress liver derived CD49a+ NK cells in response to C. albicans through unknown mechanisms[73].…”
Section: Figurementioning
confidence: 99%
“…1,2 Most of these infections are caused by Candida albicans, non-albicans Candida spp., Candida tropicalis, Candida glabrata, and Candida Krusei. 3,4 Echinocandins, polyenes, pyrimidine, allylamine, and azoles are the most common antifungal agents available for the treatment of topical Candida spp. infections.…”
Section: Introductionmentioning
confidence: 99%